EMOTIONAL DETERMINANT OF INTERNET SEXTING AMONG ADOLESCENT IN RIVERS STATE - Kelechi, Ukwuije, Chinedu; Onyenma, Olive Obioma- (IJRDO- Journal of Educational Research, 2023)
The study investigates the emotional determinant of internet sexting among adolescent in Rivers State. The study adopted descriptive research design. The population of the study was 50,568 adolescence students. Multistage sampling was used for the study which involves stratified random sampling, simple random sampling by balloting method and proportionate random sampling. A questionnaire tagged “Emotional Determinant of Internet Sexting among Adolescent Questionnaire” (EDISAQ) was used to collect data for the study. The reliability of the instrument was 0.87. Two research questions and two hypotheses were formulated for the study. The data collected were analyzed with Mean and standard deviation is used to answer the research question while t-test was used to test the corresponding null hypothesis. From the analysis, it is therefore concluded that guilt does not significantly determine internet sexting among adolescence in secondary adolescent school in Rivers State. Also, the result of the finding shows that loneliness significantly determines internet sexting among adolescence in secondary adolescent school in Rivers State. Based on the findings, it was recommended that adolescence that feels lonely or isolated from loved once should talk to a professional. Psychologists and other mental health professionals can help you express and manage your feelings and find healthy coping tools.